Human Freedom and Effective Corporate Income Tax Rates of CEE Listed Companies - Marina Purina (European Financial and Accounting Journal, 2021)
This paper analyses firm-specific and country-specific factors that have an impact on the effective corporate income tax rates (ETR) for CEE listed companies based on data obtained from the BvD Amadeus database. Business factors analysed in this research are the company size, leverage, capital and inventory intensity, and return on assets. Concerning the country-specific factors, chosen were the statutory corporate income tax rate and cultural factors represented by personal and economic freedoms covered by the Human Freedom Index (HFI), making this study different from others. The tested hypotheses predict significance of all the stated variables. Nine models were analysed based on three ETR denominators (EBT; turnover; cash flow) and three groups of countries (whole sample; sample excluding Russia; sample consisted of Bulgaria, Croatia, Poland, and Romania). Based on the panel data regression analysis and particularly the Feasible Generalised Least Squares estimator, a significant impact on the ETR was found for all variables in all the models. The main variable of interest, the HFI, came always with a negative coefficient demonstrating that, for CEE countries, a higher level of freedom is associated with a lower ETR. Findings for the remaining variables are in line with the existing literature.
Keywords: H25; M41; 650; Effective corporate tax rate; Firm-specific factors; Country-specific factors; Human Freedom Index